Advances in multi-modal non-invasive imaging techniques in the diagnosis and treatment of polypoidal choroidal vasculopathy - Wang, Yuelin; Gu, Xingwang; Chen, Youxin (Frontiers in Medicine, 2023)
Polypoidal choroidal vasculopathy (PCV) is a disease characterized by sub- retinal pigment epithelium (RPE) orange-red polypoidal lesions and abnormal branching neovascular networks (BNNs). In recent years, various non-invasive imaging technologies have rapidly developed, especially the emergence of optical coherence tomography angiography (OCTA), multi-spectral imaging and other technologies, which enables to observe more features of PCV. Besides, these technologies are faster and less invasive compared to indocyanine green angiography (ICGA). Multi-modal imaging, which combined multiple imaging techniques, provides important references for the diagnosis and treatment of PCV with the assistance of regression models, deep-learning and other algorithms. In this paper, we review the noninvasive imaging techniques, multimodal imaging diagnosis and multi-scene therapeutic applications of PCV, with the aim of providing a reference for non-invasive multi-modal diagnosis and treatment of PCV.